ANALISIS PENDAPATAN USAHA TERNAK AYAM PEDAGING (STUDI KASUS PADA USAHA ”PATRIOT”) DI DESA MASARI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MAUTONG PROVINSI SULAWESI TENGAH - Setiawan, I Nyoman Agus; Hadayani, Hadayani; Lamusa, Arifuddin (AGROTEKBIS, 2018)
This study aims to determine the income of broiler farms in Masari Village. This research has been conducted on patriot farmer's business in Masari Village in July to September 2017. Data analysis used in this research is quantitative data i.e. data in the form of numbers based on the result of questionnaire which include the result of the acceptance received (TR) reduced by the total cost incurred (TC) in one production. The result of this research was "Patriot" income in a single production process of IDR.34,639,002 obtained from the difference between revenue (TR) of IDR.121,487,705with production cost (TC) of IDR. 86,848,703.